Governance and relationship flexibility under conditions of supply market dynamism. (2017) - Atkins, Ryan
The benefits of long term buyer-supplier relationships are well-noted in supply chain management research. In quickly changing environments, however, these benefits may be diminished, at least temporarily, if the supplier is unable to support the buyer's changing needs. To address this dilemma, manufacturers can build flexibility into their supplier relationships. This research develops and tests a theoretical model relating contractual and relational governance mechanisms - contracts and long term commitment, respectively - to relationship flexibility. Based on a survey of 110 purchasing and supply chain managers, this research provides empirical evidence that both contracts and long term commitment can promote relationship flexibility, and that supply market dynamism positively moderates the effects of long term commitment on relationship flexibility and negatively moderates the effects of contracts on relationship flexibility.